PENGARUH PEMBERIAN PENGUATAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS VIII SMP NEGERI 2 KOTA SOLOK - MERIKA SETIAWATI, S.Pd,M.Pd (Menara Ilmu, 2017)
The research was motivated by the lack of learning outcomes in the learning economy students of SMP Negeri 2 Kota Solok. This is because in the process of student learning wascentered on the teacher, so that students are less motivated, in other words, students are lessattentive and actively engaged in learning activities. One way that can be done to overcomethat is by using a provision of reinforcement. This study aims to determine how the effect of thestrengthening of student learning outcomes in subjects Economics. The hypothesis in this studyare: The result of students learning in Economics study by using the provision ofreinforcement is better than learning outcomes of students learning Economics usual.The study was pre-experimental research. The population in this study were eighthgrade students of SMP Negeri 2 Kota Solok which consists of 11 classes. The samplingtechnique was purposive sampling were selected as sample class is the class VIII10. The dataanalysis technique used is the test of the difference between two mean the t test. Based on thecalculations, the TTable thitung = 4.719 and = 1.66 so tcount> ttable at 95% confidence levelmeans H0 is rejected. It can be concluded that: The result of students learn in economics studyby using the provision of reinforcement is better than learning outcomes of students learningEconomics ordinary eighth grade students of SMP Negeri 2 Kota Solok.